Teacher Effects in Germany: Evidence from Elementary School - María Daniela Araujo P.; Johanna Sophie Quis (ZBW - Leibniz Information Centre for Economics, 2021)
The value-added to student achievement model has become a key tool for estimating the effects of individual teachers and their classrooms on students' short-term academic success, and more importantly, on later-life outcomes. We use primary school data from the German National Educational Panel Study (NEPS) to estimate classroom effects on mathematical and language competence development, which are driven by teacher quality differences across classrooms. We estimate a value-added model with individual classroom fixed-, as well as random effects. Both model specifications apply empirical Bayes shrinkage to adjust the classroom effects' estimates by their level of precision. Our results show substantial classroom effects and quality differences across the first grades of German primary school. One standard deviation increase in classroom effectiveness is associated with at least a 12 percent of a standard deviation increase in student mathematical competence scores, and at least 14 percent of a standard deviation increase in language competence scores. In addition, we find that none of the teacher characteristics typically used in teacher recruitment processes significantly explain the classroom quality differences. Interestingly, as parental assessment of teacher quality is the only indicator significantly associated with classroom effectiveness in language competence development, parents seem to be able to identify more effective language teachers.
Keywords: I20; J45; 330; classroom effects; teacher effects; teacher value-added; Germany